Macroeconomics and health : investing in health for economic development. n macroeconomics and health. (World Health Organization, 2001)
In response to the need to place health at the centre of the development agenda, the Director-General of WHO appointed in January 2000 a Commission on Macroeconomics and Health consisting of a group of leading economists and health experts. The commission's findings are presented in this report, which describes a new strategy for investing in health for economic development, especially in the world's poorest countries. Proposing a new global partnership of developing and developed countries, the report states that timely and bold action could save around 8 million lives each year in developing.